Catalytic study on TiO2 photocatalyst synthesized via microemulsion method on atrazine - Ruslimie .C.A; Hasmizam Razali; Wan M. Khairu (Universiti Kebangsaan Malaysia, 2011)
Titanium dioxide photocatalyst was synthesised by microemulsions method under controlled hydrolysis of titanium butoxide, Ti(O(CH2)3)CH3. The synthesised TiO2 photocatalyst was compared with Sigma-commercial TiO2 by carrying out the investigation on its properties using scanning electron microscopy (SEM), x-ray diffraction (XRD) analysis and thermal gravimetric analysis (TGA). The photocatalytic activities for both photocatalysts were studied for atrazine photodegradation.